Digital Corporate Board: A Veritable Tool for Enhancing Board Performance among Listed Consumer Goods Firms in Nigeria - Adegboyegun, Adekunle Emmanuel; Koppeschaar, Zanne Ronelle (International Review of Management and Marketing, 2026)
The adoption of digital corporate board has become a revolutionary mechanism for improving corporate governance and board effectiveness in emerging economies. Whilst digital transformation, IT governance, and technological preparedness describe broader organizational processes, digital corporate board construct isolates the board governance aspect. This paper explores the impact of digital corporate board on board performance in Nigeria. The study rested on ex-post facto research design and utilized secondary data covering the period between 2014 and 2024. The study population consists of all the Nigerian quoted consumer goods companies as at 31st December, 2024, and the entire population selected as sample size using census sampling technique. Annual reports of sampled firms were used for data collection and descriptive statistics, and robust regression analysis employed in the data analysis. The study findings revealed that board technology competency and E-portal system adoption have significant and positive impacts on board performance. The adverse influence of digital committee presence is, however, not statistically significant in board effectiveness. The study concludes that most digital board characteristics are vital in promoting the performance of corporate boards. The study suggests that organizations should focus on adding tech literates on their boards, conduct regular digital literacy training, digitalized the boardroom through adoption of E-board portal, and initiate a digital committee that is capable of bridging technology with strategic thinking. To guarantee sustainable growth in the consumer goods industry, Policy makers should formulate guidelines to standardize digital governance practices, augment oversight onus, and enhance disclosure of digital board strategies.